Seed priming boosted waxy corn yield across different water regimes - Mariano Trivandy Ngasu Nganggo; Didik Indradewa; SIti Nurul Rofiqo Irwan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Plant resistance to drought stress could be improved by seed priming using natural plant growth regulators, such as coconut water. This research aimed examine the physiological characteristics, root development, and yield responses of waxy corn following different seed priming treatmens using coconut water and to determine to the optimal coconut water concentration for seed priming under each drought condition. The research was conducted at Banguntapan Sub-district and Laboratory of the Faculty of Agriculture, Universitas Gadjah Mada, Yogyakarta - Indonesia, in July-October 2023. The research used a split-plot design with a main plot of watering intervals and a subplot of coconut water concentration with three replications. The main plot consisted of three levels: watering every day, once every three days, and once every six days. The subplot consisted of four levels of coconut water concentrations, i.e., 0, 33, 67, and 100%. The results indicated that seed priming with 100% coconut water increased corn yield. The increased yield could be attributed to the different photosynthetic rates and total seed weight under both well-watered and drought-stress conditions. Keywords: coconut water; drought stress; root improvement